1992
DOI: 10.1007/bf00006151
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tubificid oligochaetes on the uptake of zinc by Lake Erie sediments

Abstract: A laboratory experiment was conducted to determine the effect of tubificid worms on the flux of zinc into lake sediments. Forty-six cores of Lake Erie sediment, with and without (control) tubificid worm populations, were exposed to aquarium water with a zinc concentration of about 5 mg l-' for 139 days. Pore water and exchangeable particulate zinc concentrations in the top 12 cm of sediment were periodically determined in pairs of cores -one with worms and one without worms -at 1 cm depth increments. After 139… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Only the stratigraphic importance of bioturbation will be considered and discussed here. The ability of an organism to mix sediments depends on different parameters, including the type of organism involved and its size, population density and vertical distribution in the sediment (Soster et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the stratigraphic importance of bioturbation will be considered and discussed here. The ability of an organism to mix sediments depends on different parameters, including the type of organism involved and its size, population density and vertical distribution in the sediment (Soster et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the benthic groups briefly reviewed above, oligochaetes are well known to have a significant influence on stratigraphy because of their "conveyor belt" feeding (Milbrink, 1973;Davis, 1974a,b;Soster et al, 1992;Pelegri and Blackburn, 1995). Many oligochaetes feed with their heads downward in the sediment and their posterior ends upward in the water.…”
Section: Benthic Animals and Bioturbationmentioning
confidence: 99%
“…This explains the similar shape of particulate and dissolved cadmium profiles below the first millimetre. This role of tubificid in transport of metals was already put forward by Soster et al (1992) who concluded that the higher level of Zn found in the upper 3 cm of tubificid-inhabited sediments was probably caused by bioadvective particle movement and adsorption, rather than by solute diffusion.…”
Section: Cadmium Behaviour Under Tubificids Bioturbationmentioning
confidence: 91%
“…However, the complex interaction between biological transport and cadmium chemistry often impedes the straightforward interpretation and generalization of experimental observations. Soster et al (1992) and Petersen et al (1998) demonstrated that bioturbation increases the cadmium and zinc fluxes from overlying water to uncontaminated estuarine or freshwater sediments. Yet, Rasmussen et al (1998Rasmussen et al ( , 2000 observed that Arenicola marina increased the net transport of cadmium from overlying water to the sediment when the water is contaminated, but reduced the release of cadmium from contaminated sediments to overlying water that is not contaminated.…”
Section: Introductionmentioning
confidence: 97%
“…However, little work has been undertaken to evaluate these processes in sediments accumulating U in freshwater systems (Komlos et al, 2008;Phrommavanh, 2008) and the few previous studies on this topic have concerned marine ecosystems (Zheng et al, 2002;Morford et al, 2009). In freshwater, some organisms able to survive in contaminated environments, such as tubificid worms (Annelida, Clitellata, Tubificidae), are known to induce a strong sediment reworking that could impact the remobilisation of metals (Soster et al, 1992;Petersen et al, 1995;Zoumis et al, 2001;AlfaroDe-la-Torre and Tessier, 2002;Zheng et al, 2002;Ciutat and Boudou, 2003;De Haas et al, 2005;Ciutat et al, 2007). Tubificid worms represent a dominant group of freshwater benthic macro-invertebrates.…”
Section: Introductionmentioning
confidence: 99%